Analysis of Lean Process Factors to Improve Production Process Effectiveness (Case Study in BFM Pharmaceutical Industry) - Oom Oman Abdurrahman; Vita Sarasi; Iman Chaerudin; Ina Primiana; Akhmad Yunani (Operations Excellence: Journal of Applied Industrial Engineering, 2022)
BFM is a pharmaceutical company that produces bulk Tetanus Toxoid (TT). Bulk TT demand will continue to increase until 2025, while the current utilization rate has reached 97% of its design capacity. Bulk TT's current production capacity is insufficient, while the building area cannot be enlarged. This research was conducted to improve non-necessary value added by identifying and reducing waste to run well even though the production capacity is limited. Mix descriptive qualitative and quantitative methods are applied in this research. Production simulation is undertaken to reduce waste through the Gemba Kaizen approach and Kanban, while production capacity simulation is carried out using Dynamic Systems. The results of the simulations are described in the Balanced Scorecard. The research revealed there are 148 wastes consisting of 4 causes of waste in the high priority category, 20 medium priority and 124 low priority. The simulation generates a significant decrease value of the waste priority number (WPN) from 347.3 to 47.2. There was also an increase in the overall value stream. Value-added ratio (VAR) increased 12.57%, production lead time reduced 21.01%, and total cycle time decreased 11.65%. These findings indicated that the improvement was effective in eliminating waste. From the overall improvement, there was an increase in productivity of 25.0%.